Hanseníase no Amazonas: vulnerabilidade programática e indicadores operacionais - Moraes, Nicolle Gadelha de (Brasil, 2024)
Introduction: Leprosy is an infectious disease with a high potential to cause physical disabilities. Operational indicators allow for the assessment and monitoring of the quality of leprosy control services, as well as enabling the analysis of aspects related to programmatic vulnerability. Objective: To analyze programmatic vulnerability and evaluate operational indicators for leprosy control in the state of Amazonas. Method: Epidemiological study using data from the Leprosy Notification System in Amazonas (2012-2021). Operational indicators were calculated according to the Ministry of Health; programmatic vulnerability was analyzed; descriptive analyses were performed in Microsoft Excel®; and maps were created using the Quantum QGis Program. Results: From 2012 to 2021, 4,659 new cases of leprosy were reported in Amazonas. The proportion of contacts examined remained regular. However, the proportion of cure among new cases increased from 87.42% (2012-2016) to 91.71%(2017-2021) in the capital. Conclusion: The analysis of programmatic vulnerability revealed the importance of continuity of care, given the proportion of disability assessment in cure, and cases with multibacillary operational classification in diagnosis. The evaluation of operational indicators indicated a slight improvement (2017-2021) in the cure rate among new cases in the capital.